2009
DOI: 10.1007/s00534-009-0070-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal oncocytic papillary neoplasm of the bile duct: the first case of peribiliary gland origin

Abstract: We report herein the first case of intraductal oncocytic papillary neoplasm of the bile duct arising from a peribiliary gland of the left hepatic duct. The patient was a 63-year-old Japanese man. Radiological and cholangioscopic examinations revealed intraductal tumor of the left hepatic duct. After pathological diagnosis of adenocarcinoma by cholangioscopic biopsy, a surgical hepatobiliary resection was performed. Pathological examination revealed papillary tumor in the left hepatic duct. Histologically, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…Considering that BTSCs are associated with mucin-producing cells [39], our findings suggested that SAMD5 could be a novel marker for mouse BTSC located in the PGBs. Recent emerging evidence from many pathological reports have suggested that the epithelial cells residing in PBG is involved in the stem cell compartment of biliary tree [11] or cholangiocellular carcinogenesis in human [9,10,34]. Considering that neither peripheral cuboidal BECs nor LPCs expressed SAMD5, our findings supported the notion that mucin-producing CC arise from BTSCs in the PBGs, but not from peripheral intrahepatic bile ducts or LPCs.…”
Section: Discussionsupporting
confidence: 84%
“…Considering that BTSCs are associated with mucin-producing cells [39], our findings suggested that SAMD5 could be a novel marker for mouse BTSC located in the PGBs. Recent emerging evidence from many pathological reports have suggested that the epithelial cells residing in PBG is involved in the stem cell compartment of biliary tree [11] or cholangiocellular carcinogenesis in human [9,10,34]. Considering that neither peripheral cuboidal BECs nor LPCs expressed SAMD5, our findings supported the notion that mucin-producing CC arise from BTSCs in the PBGs, but not from peripheral intrahepatic bile ducts or LPCs.…”
Section: Discussionsupporting
confidence: 84%
“…As additional supporting evidence, Zen et al [26,29] reported an interesting observation that some cases of cyst-forming IPN of the bile duct were associated with glandular tissues resembling peribiliary glands in the cyst wall. Recently, Nakanishi et al [34] reported a case of oncocytic IPN of the bile duct arisen from a cystically dilated peribiliary gland.…”
Section: Discussionmentioning
confidence: 98%
“…However, recently, IPNBs that involved significantly the peribiliary glands and grossly showed cystic dilatation particularly aneurysmal or diverticular dilatation were reported [4749], suggesting that some type of IPNB may arise from the peribiliary glands located within the wall or scattered in the surrounding connective tissue of the intrahepatic large bile ducts and extrahepatic bile ducts. These lesions are proposed to be IPNBs corresponding to pancreatic IPMN of the branch duct type [49, 50].…”
Section: Pathogenesismentioning
confidence: 99%